2009
DOI: 10.1038/nrclinonc.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and pregnancy: how safe is trastuzumab?

Abstract: Cessation of trastuzumab and close monitoring of mother and fetus during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Patients who were exposed to trastuzumab for more than one trimester (i.e., prolonged exposure) were associated with the highest risk of complications, while those who got pregnant during drug administration and discontinued the drug once pregnancy was diagnosed did not seem to be at a considerable risk [40,50,51].…”
Section: Trastuzumab In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who were exposed to trastuzumab for more than one trimester (i.e., prolonged exposure) were associated with the highest risk of complications, while those who got pregnant during drug administration and discontinued the drug once pregnancy was diagnosed did not seem to be at a considerable risk [40,50,51].…”
Section: Trastuzumab In Pregnancymentioning
confidence: 99%
“…In this setting, trastuzumab should be stopped and we believe that pregnancy could be allowed to continue without promotion for abortion for those patients who are willing to preserve their pregnancy. Only three patients were reported to adopt this approach with no pregnancy complications observed at all [40,50,51]. There are ongoing efforts to collect the pregnancy events observed in the large adjuvant trastuzumab studies (~10,000 randomized patients) to better define the complications observed when patients unintentionally became pregnant during the course of therapy.…”
Section: Trastuzumab In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Each pregnancy resulted in the birth of a healthy baby [67][68][69]. Another case described a pregnancy exposed to trastuzumab until 24 weeks of gestation.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Multi agent AC or high dose of a single drug increase this risk. Data regarding the experience with the different anti-cancer drug that are more commonly used during pregnancy are presented in Table I (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). For more details the reader is referred to the CCOPE database (www.motherisk.org).…”
mentioning
confidence: 99%